WHO ARE THE BRAZILIANS TOBACCO GROWERS THAT BREACH THEIR CONTRACTS WHIT THE INDUSTRY? - Moreira Begnis, Heron Sergio; Arend, Silvio Cesar; Alievi, Rejane Maria (RACE - Revista de Administração, Contabilidade e Economia, 2016)
Based on the Transaction Costs and inter-organizational relations literature, this study analyzes the socioeconomic characteristics of the growers who may be related to opportunistic behavior and contract breach in the tobacco chain in South Brazil. In terms of its contractual relations, tobacco production chain is very little explored, although the contractual terms are determinants in Integrated Production Systems (IPS). The nature of this research is quantitative and the data were collected through a survey with tobacco growers from the three states of South Brazil. The analysis showed the main characteristics of the tobacco growers who are more likely to breach their contracts with integrative companies. Keywords: Contract Breach. Integrated Production System (IPS). Opportunism. Tobacco.